Analisa Hukum Pelepasan Hak Keperdataan Tanah Hak Milik Menjadi Hak Guna Bangunan Bagi Badan Usaha Melalui Pembebasan Serta Implikasinya Terhadap Daya Tarik Investasi - Jaya Jaya; atma suganda; Idzan Fautanu (Jurnal Penelitian Hukum Legalitas, 2022)
The juridical provisions governing the existence of land are contained in Law Number 5 of 1960 (UUPA). The land rights contained in the UUPA will give rise to civil rights for the community and business entities, namely through the transfer of property rights to building use rights. The method used in this study is the normative juridical method or legal research literature. The data used are primary and secondary data. The data were collected using library or document techniques and interviews. The data that has been obtained is then analyzed using a qualitative juridical method. The results showed that the implementation of the release of the original land rights followed by the determination of the granting of land rights from Property Rights into Building Use Rights. Business Entities will become unattractive to investors in investing in Indonesia if the obstacles do not get legal guarantees from the government, especially in the utilization and use of land with respect to the period of Building Use Rights with a certain time limit, which can be extended according to applicable regulations.